MODIFIED SULFUR ISOTOPIC COMPOSITIONS OF SULFIDES IN THE NAKHLITES AND CHASSIGNY - Greenwood J.P.; Riciputi L.R.; McSween H.Y.; Taylor L.A. (My University, 2000)
Variable sulfur isotopic ratios of sulfide minerals in the nakhlites and Chassigny have been measured by ion microprobe. The ranges and means of δ34S values of pyrrhotite and pyrite in nakhlites become more negative in the sequence Nakhla (δ34S: -1.7 to +4.9%%; mean δ34S = +1.5 +/- 2.0%%) > Governador Valadares (δ34S: -2.4 to +3.8%%; mean δ34S = +0.7 +/- 2.4%%) > Lafayette (-6.1 to +0.1%%; mean δ34S = -3.2 +/- 2.1%%). This is also the sequence of increasing degrees of subsolidus re-equilibration, suggesting that 32S enrichment may be related to the subsolidus thermal history. A chalcopyrite vein cross cutting a pyrrhotite in Nakhla, coupled with chalcopyrite having slightly lighter δ34S values, suggests that subsolidus fluids may have become isotopically lighter (with respect to sulfur) in Nakhla with time. Pyrite has replaced pyrrhotite in Lafayette, suggesting that fO2 and/or fS2 increased after pyrrhotite crystallization. A model involving subsolidus hydrothermal modification of igneous sulfide minerals (with δ34S ~ 0%%) due to late-stage oxidation of fluids provides a reasonable explanation for the sulfur isotopic systematics of the nakhlites and Chassigny. Sulfur isotopic alteration is believed to have occurred during the waning stages of nakhlite magmatism, rather than during a much later low-temperature (<100°C) iddingsite formation event, based on the ineffectiveness of abiogenic sulfur isotopic fractionation below 200°C. Variable mixing of two isotopically different fluids also could have produced the observed fractionations, although an isotopically light reservoir of sulfur is problematic. Other possible mechanisms evaluated to explain the sulfur isotopic values of the sulfide minerals include martian mantle heterogeneity, possible influence of martian biological processes, and magmatic degassing of SO2.